Antibacterial Activity of Bis (2-Ethylhexyl) Phthalate Leaves Fraction of Colocacia esculenta L against Enteric Gram Negative Bacteria - Herwin Herwin; Siska Nuryanti; Muzakkir Baits; Sjafaraenan Sjafaraenan (Journal of Global Pharma Technology, 2020)
This study is aimed at testing the antibacterial activity of the compound Bis (2-Ethylhexyl) phthalate leaves fraction of Colocacia esculenta L against enteric gram negative bacteria. The search for bioactive compounds employs the vacuum liquid chromatography method used for fractionation and purification, spectroscopic analysis (infrared, proton and carbon core magnetic resonance, chromatography-mass spectroscopy) gas, Minimal Inhibitory Concentration (MIC), Minimal Bactericidal Concentration (MBC), Agar diffusion and TLC-Bioautography for activity testing against Enteric Gram Negative Bacteria. The results of the fractionation shows that based on agar diffusion, the B fraction obtains the MIC value is 0.1%, and MBC value is 1%. Spectroscopic analysis of the secondary metabolites of the leaves fraction of Colocacia esculenta L obtains the chemical structure of Bis (2-Ethylhexyl) phthalate with the molecular formula C24H38O4 and molecular weight 390.5. The test on the compound Bis (2-Ethylhexyl) phthalate from the leaves fraction of Colocacia esculenta L L by TLC-Bio autography obtains an active Rf value of 0.7 against bacteria Escherichia coli, Pseudomonas aeruginosa, Salmonella thypi, Streptococcus mutans, and Vibrio cholerae, by diffusion Agar method, the largest inhibition zone in Salmonella thypi bacteria. Based on the results, the identification of secondary metabolites from the leaves fraction of Colocacia esculenta L obtains the chemical compound Bis (2-Ethylhexyl) phthalate and based on the results of the antibacterial activity test of the chemical compound Bis (2-Ethylhexyl) phthalate leaves of Colocacia Esculenta L is potential for the treatment of enteric gram negative bacteria infections. Keywords: Colocacia esculenta L, Bis (2-Ethylhexyl) phthalate, Antibacterial